Network Analysis of Plasmidomes: The Azospirillum brasilense Sp245 Case - Orlandini, Valerio (Int J Evol Biol, 2014)
Azospirillum brasilense is a nitrogen-fixing bacterium living in association with plant roots. The genome of the strain Sp245, isolated in Brazil from wheat roots, consists of one chromosome and six plasmids. In this work, the A. brasilense Sp245 plasmids were analyzed in order to shed some light on the evolutionary pathways they followed over time. To this purpose, a similarity network approach was applied in order to identify the evolutionary relationships among all the A. brasilense plasmids encoded proteins; in this context a computational pipeline specifically devoted to the analysis and the visualization of the network-like evolutionary relationships among different plasmids molecules was developed. This information was supplemented with a detailed (in silico) functional characterization of both the connected (i.e., sharing homology with other sequences in the dataset) and the unconnected (i.e., not sharing homology) components of the network. Furthermore, the most likely source organism for each of the genes encoded by A. brasilense plasmids was checked, allowing the identification of possible trends of gene loss/gain in this microorganism. Data obtained provided a detailed description of the evolutionary landscape of the plasmids of A. brasilense Sp245, suggesting some of the molecular mechanisms responsible for the present-day structure of these molecules.